2014
DOI: 10.1016/j.ijpharm.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol-phosphatidylethanolamine (PEG-PE)/vitamin E micelles for co-delivery of paclitaxel and curcumin to overcome multi-drug resistance in ovarian cancer

Abstract: The therapeutic potential of mixed micelles, made of PEG-PE and vitamin E co-loaded with curcumin and paclitaxel, was investigated against SK-OV-3 human ovarian adenocarcinoma along with its multi-drug resistant version SK-OV-3-paclitaxel-resistant (TR) cells in vitro and in vivo. The addition of curcumin at various concentrations did not significantly enhance the cytotoxicity of paclitaxel against SK-OV-3 in vitro. However, a clear synergistic effect was observed with the combination treatment against SK-OV-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 21 publications
8
57
0
Order By: Relevance
“…In reported studies, there have been many examples of applying Cur in combination therapies. Abouzeid et al 57 codelivered Cur and paclitaxel, and they observed a clear synergistic effect against SKOV-3TR cells. Carlson et al 58 found that the combination of resveratrol and Cur were also synergistic in inhibiting SKOV3 cell proliferation.…”
mentioning
confidence: 99%
“…In reported studies, there have been many examples of applying Cur in combination therapies. Abouzeid et al 57 codelivered Cur and paclitaxel, and they observed a clear synergistic effect against SKOV-3TR cells. Carlson et al 58 found that the combination of resveratrol and Cur were also synergistic in inhibiting SKOV3 cell proliferation.…”
mentioning
confidence: 99%
“…It is well known that the interaction between hydrophobic drugs and the micelle core environment is a very important factor in micelle stability. 50 After reconstituting the lyophilized micelles in aqueous solutions in the present study, the hydrophobic segment of Figure 8 The appearances of DMc-PMs before lyophilization (A), lyophilized powder (B), and reconstituted solution (C). Abbreviation: DMc-PMs, dimethoxycurcumin-loaded polymeric micelles.…”
Section: In Vitro Stabilitymentioning
confidence: 82%
“…Cisplatin and paclitaxel PEG-PGlu90-PPhe25 hybrid micelles Ovarian cancer [56] Linear-dendritic telodendrimer micelles Ovarian cancer [57] Doxorubicin and disulfiram Polymeric micelles Breast cancer [58] Doxorubicin and curcumin Polymeric micelles Breast cancer [59] Doxorubicin and paclitaxel Pluronic mixed micelles Breast cancer [60] Docetaxel and chloroquine PEO-PPO-PCL/TPGS micelles Breast cancer [61] Paclitaxel and curcumin PEG-PE and vitamin E micelles Ovarian cancer [62] In order to eradicate ovarian cancer, Desale et al [56] synthesized biodegradable triblock copolymers containing ethylene glycol, glutamic acid, and phenylalanine (PEG-PGlu-PPhe). These copolymers self-assembled to form micelles for the co-delivery of CDDP and PTX, and the resulting nanomedicine mounted strong tumor suppression effects both in vitro and in vivo.…”
Section: Combined Chemotherapeuticsmentioning
confidence: 99%